2010
DOI: 10.1080/00221320903548118
|View full text |Cite
|
Sign up to set email alerts
|

Spaced Retrieval Enhances Memory for a Name-Face-Occupation Association in Older Adults With Probable Alzheimer's Disease

Abstract: The authors trained 4 older adults with probable Alzheimer's disease to recall a name-face-occupation association using the spaced retrieval technique. Six training sessions were administered over a 2-week period. On each trial, participants selected a target photograph and stated the target name and occupation at increasingly longer retention intervals, contingent upon successful recall. Two transfer tasks were included to determine whether the trained association transferred to the person whose picture serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 14 publications
1
37
0
1
Order By: Relevance
“…For example, spaced retrieval requires the patient to remember targeted information over progressively longer delays whereas the technique of subtracting cues gradually removes aspects of the target information (e.g., the letters of a name) over successive exposures. These techniques have demonstrated efficacy in patients who have progressed to AD (Cherry, Walvoord, & Hawley, 2010;Small, 2012); results that reinforce our above conclusion that rehearsal may be most appropriate for late MCI patients. These techniques are effective for teaching specific information Sitzer, Twamley, & Jeste, 2006) (e.g., the names of new church members) but it is critical to understand that the effects are stimulus/information specific and unlikely to generalize (e.g., to other church members or new members of a Senior Center).…”
Section: Common Approachessupporting
confidence: 72%
“…For example, spaced retrieval requires the patient to remember targeted information over progressively longer delays whereas the technique of subtracting cues gradually removes aspects of the target information (e.g., the letters of a name) over successive exposures. These techniques have demonstrated efficacy in patients who have progressed to AD (Cherry, Walvoord, & Hawley, 2010;Small, 2012); results that reinforce our above conclusion that rehearsal may be most appropriate for late MCI patients. These techniques are effective for teaching specific information Sitzer, Twamley, & Jeste, 2006) (e.g., the names of new church members) but it is critical to understand that the effects are stimulus/information specific and unlikely to generalize (e.g., to other church members or new members of a Senior Center).…”
Section: Common Approachessupporting
confidence: 72%
“…Thus, SR does not rule out the possibility of errors occurring, but in practice, because the initial recall intervals are kept very short, errors are rare and may sometimes be eliminated entirely. Reports indicate that SR can produce effective learning in people with brain injury (e.g., Melton and Bourgeois 2005) and people with dementia (Abrahams and Camp 1993;McKitrick and Camp 1993;Camp et al 1996;Cherry et al 1999;Hawley and Cherry 2004). Bourgeois et al (2003) found SR more effective than a cueing hierarchy in teaching people with dementia a strategy involving an external memory aid.…”
Section: Methodological Issuesmentioning
confidence: 96%
“…Work by Camp and colleagues (e.g., Camp, Foss, O'Hanlon, & Stevens, 1996;Cherry, Simmons, & Camp, 1999) has shown that instrumental functioning in memory-impaired older individuals can be supported by training them with spaced-retrieval techniques to remember how to seek needed support. Spaced retrieval involves practicing the retrieval of information until it can be accessed.…”
Section: Cognitive-training Studiesmentioning
confidence: 99%